Mineral oil barrier is an effective alternative for suppression of damage by white snails - Mehraneh Sepasi; Mohammad Reza Damavandian; Behnam Amiri Besheli (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2019)
Purpose: Citrus white snail, Helicella candeharica Pfeiffer (Panpulmonata: Helicidae) is one of the most important orchard pests. In this study, the effectiveness of mineral oil was compared with molluscicide baits such as metaldehyde, ferricole (iron phosphate) and a snail-repellent paint in a commercial citrus orchard in northern Iran to reduce access of citrus white snails to citrus trees. Materials and methods: The number of snails on citrus trees was monitored and counted 10 days after the application of the treatments, and at an interval of 6–8 days up to harvest time. Results: In the first study, the mineral oil and repellent paint treatments reduced a number of snails best. In the second study, using metaldehyde and mineral oil barrier, again the mineral oil barrier reduced snails best. The cost of each treatment during one season per hectare was calculated at 55, 153, 124 and 120 $/ha for mineral oil, iron phosphate, snail-repellent paint and metaldehyde, respectively. Conclusions: Mineral oil is an effective alternative for chemical compounds for reducing access by H. candeharica to citrus trees.